2006
DOI: 10.1038/sj.ejhg.5201677
|View full text |Cite
|
Sign up to set email alerts
|

Association of a 31 bp VNTR in the CBS gene with postload homocysteine concentrations in the Framingham Offspring Study

Abstract: Elevated total plasma homocysteine concentrations (tHcy), both fasting and post-methionine load, have been established as risk factors for vascular disease. Recently, we described the association of a 31 bp variable number of tandem repeats (VNTR) in the cystathionine b-synthase (CBS) gene with both CBS enzyme activity and tHcy concentrations. In the present study, we determined the 31 bp VNTR genotypes in 2598 individuals of the Framingham Offspring Study and studied the association between this genotype and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Long alleles of this VNTR are known to be associated with elevated Hcy levels and lower CBS activity indicating a disturbed Hcy homeostasis. 27,28 We performed two genetic association studies with three CBS markers in case-control samples from different European countries, which was suggested to be advantageous. 37 We demonstrated an association of CBS VNTR alleles at the exon 15-intron 15 boundary with susceptibility to severe sepsis/septic shock in both German and Greek samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long alleles of this VNTR are known to be associated with elevated Hcy levels and lower CBS activity indicating a disturbed Hcy homeostasis. 27,28 We performed two genetic association studies with three CBS markers in case-control samples from different European countries, which was suggested to be advantageous. 37 We demonstrated an association of CBS VNTR alleles at the exon 15-intron 15 boundary with susceptibility to severe sepsis/septic shock in both German and Greek samples.…”
Section: Discussionmentioning
confidence: 99%
“…So far, this VNTR was associated with plasma Hcy levels following postmethionine load. 27,28 Thus, it seems reasonable to investigate linkage disequilibrium (LD) of the VNTR alleles with those of rs6586282 given that the VNTR might be the functional variation causing the observed CBS associations.…”
Section: Introductionmentioning
confidence: 99%
“…end of exon 13 and extends 19 bp into intron 13 (Yang et al 2000). The number of repeat units of this VNTR varies between 15 and 21 (except for 20) in different alleles (Lievers et al 2001(Lievers et al , 2006Afman et al 2003;Beyer et al 2004). Studies have demonstrated a negative association between CBS enzyme activity and the number of repeat units (Lievers et al 2001), as well as a positive association between the number of repeat units and postload plasma Hcy concentrations (Lievers et al 2001(Lievers et al , 2006.…”
Section: Introductionmentioning
confidence: 99%
“…The number of repeat units of this VNTR varies between 15 and 21 (except for 20) in different alleles (Lievers et al 2001(Lievers et al , 2006Afman et al 2003;Beyer et al 2004). Studies have demonstrated a negative association between CBS enzyme activity and the number of repeat units (Lievers et al 2001), as well as a positive association between the number of repeat units and postload plasma Hcy concentrations (Lievers et al 2001(Lievers et al , 2006. Since the postload Hcy concentrations were found to be associated with an increased risk for cardiovascular disease (CVD) (Bostom et al 1995;Verhoef et al 1997), this 31-bp VNTR may serve as a risk factor for CVD.…”
Section: Introductionmentioning
confidence: 99%
“…Increased homocysteine concentrations are also associated with inadequate intakes of a variety of B vitamins, including riboflavin, vitamin B6, and vitamin B12 [14,15], and genetic variation in the MTHFR and CβS genes [16,17]. Linkage studies have identified an association between low BMD with the 1p36 region on chromosome 1 in the vicinity of the MTHFR gene [18,19].…”
Section: Introductionsmentioning
confidence: 99%